Breaching the Castle Walls: Hyaluronan Depletion as a Therapeutic Approach to Cancer Therapy - Shepard, H. Michael (Frontiers in Oncology, 2015)
Hyaluronan (HA) has many functions in the extracellular milieu of normal and diseased tissues. Disease-associated HA accumulation has been shown to predict a worsened prognosis in cancer patients, with tumors having a high extracellular HA content (HA-high) being more aggressive than their HA-low counterparts. HA-high tumor aggressiveness is derived from the specialized biomechanical and molecular properties of the HA-based assembly of HA binding proteins and the growth-promoting factors that accumulate in it. Biophysical characteristics of an HA-high tumor microenvironment include high tumor interstitial pressure, compression of tumor vasculature, and resulting tumor hypoxia. Within the tumor cell membrane, HA receptors, primarily CD44 and RHAMM, anchor the HA-high extracellular network. HA-CD44 association on the tumor cell surface enhances receptor tyrosine kinase activity to drive tumor progression and treatment resistance. Together, malignant cells in this HA-high matrix may evolve dependency on it for growth. This yields the hypothesis that depleting HA in HA-high tumors may be associated with a therapeutic benefit. A pegylated form of recombinant human hyaluronidase PH20 (PEGPH20) has been deployed as a potential cancer therapeutic in HA-high tumors. PEGPH20 can collapse this matrix by degrading the HA-assembled tumor extracellular framework, leading to tumor growth inhibition, preferentially in HA-high tumors. Enzymatic depletion of HA by PEGPH20 results in re-expansion of the tumor vasculature, reduction in tumor hypoxia, and increased penetration of therapeutic molecules into the tumor. Finally, HA depletion results in reduced signaling via CD44/RHAMM. Taken together, HA-depletion strategies accomplish their antitumor effects by multiple mechanisms that include targeting both biophysical and molecular signaling pathways. Ongoing clinical trials are examining the potential of PEGPH20 in combination with partner therapeutics in several cancers.